2010
DOI: 10.3945/ajcn.2009.28728
|View full text |Cite
|
Sign up to set email alerts
|

Is protein intake associated with bone mineral density in young women?

Abstract: Data from this longitudinal study suggest that a higher protein intake does not have an adverse effect on bone in premenopausal women. Cross-sectional analyses suggest that low vegetable protein intake is associated with lower BMD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
2
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 40 publications
0
34
2
2
Order By: Relevance
“…They conclude that dietary proteins, if not significantly favorable, are at least not detrimental to bone density. In addition, a recent longitudinal study including 540 premenopausal women found no adverse effect of increased protein intakes (from 5 to 25% of the energy intake) on BMD (Beasley et al, 2010). Studies frequently cited to support the deleterious effect of HP diet on bone health are retrospective analyses of hip fracture incidence in postmenopausal women of different countries (Abelow et al, 1992;Frassetto et al, 2000), which found that the highest rate of hip fractures occurred in industrialized Western countries, which have the highest animal protein intake.…”
Section: Protein Intake and Bone Healthmentioning
confidence: 99%
“…They conclude that dietary proteins, if not significantly favorable, are at least not detrimental to bone density. In addition, a recent longitudinal study including 540 premenopausal women found no adverse effect of increased protein intakes (from 5 to 25% of the energy intake) on BMD (Beasley et al, 2010). Studies frequently cited to support the deleterious effect of HP diet on bone health are retrospective analyses of hip fracture incidence in postmenopausal women of different countries (Abelow et al, 1992;Frassetto et al, 2000), which found that the highest rate of hip fractures occurred in industrialized Western countries, which have the highest animal protein intake.…”
Section: Protein Intake and Bone Healthmentioning
confidence: 99%
“…Data indicate that protein source (animal or vegetable) may influence the relationship between protein intake and bone health because protein from animal sources is high in acidic amino acids such as cysteine and methionine,3 although these acidic amino acids are also found in plant‐based sources such as nuts. Three recent studies have shown that vegetable protein, but not animal protein, is associated with increased BMD in women 10, 11, 12. Conversely, in a study of 562 women, increased intake of 15 g animal protein per day was associated with increased BMD at the hip (0.016 g/cm 2 ) and femoral neck (0.012 g/cm 2 ), and a 15 g/day increase in vegetable protein intake was associated with lower BMD at the hip (–0.013 g/cm 2 ) and femoral neck (–0.010 g/cm 2 ),13 and in a study of post‐menopausal women the relative risk of hip fracture was found to decrease significantly across increasing quartiles of animal protein intake (1.00 [reference]; 0.59 [95% CI, 0.3 to 1.3]; 0.63 [95% CI, 0.3 to 1.4]; and 0.31 [95% CI, 0.1 to 0.9]) 14…”
Section: Introductionmentioning
confidence: 99%
“…BMD was positively associated with animal protein intake and negatively to vegetable intake in one study (Promislow et al, 2002) but the opposite association was found when considering bone ultrasound attenuation (Weikert et al, 2005). Low levels of both protein types have been associated with deleterious effects on bone: low animal protein is related to bone loss (Hannan et al, 2000) and low vegetable protein is related to low BMD (Beasley et al, 2010). These results suggest that a minimum intake of both proteins is required regardless of the source.…”
Section: Animal Vs Vegetable Proteinmentioning
confidence: 68%
“…On the other hand, two studies on premenopausal women concluded that protein intake had no relation with BMD (Beasley et al, 2010;Mazess & Barden, 1991). One study reported a negative association with BMC (Metz et al, 1993).…”
Section: Protein and Bone Parameters 41 Bone Mineral Densitymentioning
confidence: 99%